2012
DOI: 10.1080/13825585.2011.629290
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, daily living, and health-related quality of life in 85-year-olds in Sweden

Abstract: This study investigates how cognition influences activities of daily living and healthrelated quality of life in 85-year-olds in Sweden (n=373). Data collection included a postal questionnaire comprising demographics and health-related quality of life measured by the EQ-5D. The ability to perform personal activities of daily living was assessed during a home visit that included administering the Mini Mental State Examination (MMSE). Cognitive impairment was shown in 108 individuals (29%). The majority were ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 31 publications
6
26
0
1
Order By: Relevance
“…The results also showed that MMSE scores, a measure of cognitive function, were significantly associated with HRQL scores after accounting for known covariates in a way which, changes in MMSE scores resulted in changes in HRQL scores after adjusting for potential confounders. In a similar community based survey, Pan et al found that QOL scores were significantly lower in older adults with cognitive dysfunction (13), while in another study in Sweden, cognitive decline was not associated with all dimensions of HRQL in nursing home residents (16); and Davis et al, in a study on community dwelling older adults found relation between only cognitive function and well-being and not HRQL (37). Doordian found that not only cognitive function, but also changes in cognitive function had significant crude association with HRQL, but after adjusting for covariates of depression, age and functional dependence, this association lost its significant (38).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The results also showed that MMSE scores, a measure of cognitive function, were significantly associated with HRQL scores after accounting for known covariates in a way which, changes in MMSE scores resulted in changes in HRQL scores after adjusting for potential confounders. In a similar community based survey, Pan et al found that QOL scores were significantly lower in older adults with cognitive dysfunction (13), while in another study in Sweden, cognitive decline was not associated with all dimensions of HRQL in nursing home residents (16); and Davis et al, in a study on community dwelling older adults found relation between only cognitive function and well-being and not HRQL (37). Doordian found that not only cognitive function, but also changes in cognitive function had significant crude association with HRQL, but after adjusting for covariates of depression, age and functional dependence, this association lost its significant (38).…”
Section: Discussionmentioning
confidence: 97%
“…A study on Chinese elderly by Pan et al showed that negative impact on HRQL was increased by the severity of cognitive dysfunction (13). Akday et al also suggested cognitive impairment results in low scores in some areas of HRQL in Turkish elders (14); on the other hand, Missotten et al found that only dementia, not mild cognitive impairment (MCI), is related to HRQL in older Belgian people (15), and Johansson et al found low but significant correlation between HRQL and cognitive function in 85-year-olds in Sweden (16); finally, Elliot et al suggested that cognitive impairment did not modify HRQL (17). As presented above, the results of previous studies vary considerably based on settings, study populations and conditions.…”
Section: Introductionmentioning
confidence: 99%
“…As population ages, risks for decline in cognitive function threaten the independence and quality of life of older people and challenge the health care system (Dodge et al 2005;Johansson et al 2012). However, there is great variability among older persons in the rate of decline across various domains of cognitive performance (Wilson et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Using the SF-12 responses, we calculated each patient's Physical Component Score (PCS), which ranges between 0 to 100, and a score of 50 indicating median HRQOL related to physical function. 20 The PCS is correlated with severity of chronic disease symptoms 20 and with function 21-23 and has been used previously as an outcome of quality of chronic disease care. 2 Therefore, we used the PCS as a potential outcome of better AQQ-16 and AQF-5 scores.…”
Section: Methodsmentioning
confidence: 99%